PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP MINAT BELI KONSUMEN YANG DI MEDIASI OLEH BRAND IMAGE DAN BRAND TRUST (STUDI PADA KONSUMEN TENUN IKAT â€œARIMBIâ€ KABUPATEN SRAGEN) - Panglipurningrum, Yofhi Septian; Sulistiyani, Reny Dwi; Dewi, Septiana Novita (Jurnal Bulletin, 2018)
Effect of Product and Price Quality on Consumer Buying Interests Mediated by Brand Image and Brand Trust (Study on Consumers of Ikat "ARIMBI" in Sragen Regency). The development of fashion design in this modern era has experienced a very rapid development, even consumers' buying interest has shifted to modern designs and most of them forget about traditional products one of which is ikat weaving. Sragen Regency has a weaving industry that has been started since 2012. Typical Sragen woven fabric "Arimbi". Is one of the many traditional woven fabric products similar in Indonesia. Looking at this phenomenon, the research team proposed research related to the role of brand image and brand trust as a mediating variable between product quality and price to consumer buying interest, this was intended to make the weaving industry know what factors were causing consumers' interest in buying crafts. "ARIMBI" woven cloth is one of the superior products of Sragen Regency. The population in this study were consumers who wore "Arimbi" weaving in Sragen Regency. In this study the number of consumers using woven fabric "Arimbi: not known with certainty so to calculate the minimum number of samples needed using the Lemeshow formula with a sample of 150 respondents. The sampling technique in this study using convenience sampling with the analysis method used is path analysis (path analysis). The results of this study indicate that product quality has a significant effect on brand image. Prices have a significant effect on brand image. Product quality has a significant effect on brand trust. Prices have a significant effect on brand trust. Product quality has a significant effect on buying interest. Prices have a significant effect on buying interest. Brand image has a significant effect on buying interest. Brand trust has a significant effect on buying interest. Path Analysis Results: the effect of product quality and price on buying interest through brand image is smaller than the direct effect so that the most effective path is direct path. The effect of product quality and price on buying interest through brand trust is less than the direct influence so that the most effective pathway is the direct path. Product quality variables are the most dominant variables in influencing consumers' buying interest of "Arimbi" Ikat Weaving in Sragen Regency.